The Effect of Electroporation Method towards the Motility and Viability of Java Barb Fish (Puntius javanicus) Sperm - Rikianto, Dimas Adetia; Soeprijanto, Agoes; Kilawati, Yuni (The Journal of Experimental Life Science, 2017)
Electric shock treatment of Java Barb Fish (Puntius javanicus) sperm using electroporation method on sperm as transfer gen (Sperm Mediated Gen Transfer) has not been implemented in Indonesia. This study was conducted to know the effect of electric shock using gene pulser at different voltage level toward motility and viability of Java barb fish sperm. This research was conducted at Fish Breeding Laboratory, Faculty of Marine and Fisheries and LSIH of Brawijaya University-Malang in May 2017. The trial design used Complete Randomized Design with 3 different treatments and 1 control which each treatment repeated 3 times. The treatments used the Gene pulser with 3 different voltages: A (20 V), B (30 V), C (40 V). The result showed that the electric shock treatment with different voltages level affected motility and viability of Java barb fish sperm. Based on the data analysis used polynomial orthogonal, a linear-form of the relationship among the treatments in the form of equation was found (Puntius javanicus) with R2=0.9815 and equation y = -40.5x + 130.83 with R2= 0.8626. Based on the result of this research, electroporation for Java barb fish' sperm as gene transfer media should be done with voltage 20 V, pulse number 4 times and pulse length 1 ms. Keywords: electroporation, motility, Puntius javanicus, sperm, viability.